Protocol H - Induction of gynogenesis using UV-light and cold shock [Pratical guide of protocols: chromosome set manipulation] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
Gynogenesis is a term that describes exclusively maternal uniparental inheritance. The main goal of this Protocol is to induce gynogenesis in the European sea bass using an optimized protocol based on: (i) UV-irradiation for sea bass sperm genome inactivation (Protocol G); and (ii) cold-shocking of the eggs to inhibit the extrusion of the second polar body (i.e., restoration of diploidy) to produce partially inbred fish, called meiogynogen diploids. The contribution of several factors to mortality of meiogynogenetic sea bass during early development and sex ratios in meiogynogenetic sea bass are also discussed.